The implementation of the Homelessness Reduction Act 2017: an empirical study - Reeson, Carla (2023)
This thesis is a socio-legal study of the implementation of the Homelessness Reduction Act 2017, an ambitious piece of legislative reform introducing new statutory duties on local authorities in England to intervene earlier to prevent and relieve homelessness. It analyses original findings from in-depth ethnographic case studies in two local authority housing departments in the Midlands to explore how the Act was implemented on the frontline. It utilises a Foucauldian theoretical framework to explore how new duties are performed, how housing officers perceive their role after the Act, and how homelessness and the individual experiencing homelessness are governed. The thesis finishes by concluding that while the Act is a step in the right direction, it struggles to deliver on its bold title, failing to make any substantial strides in reducing homelessness. There is a clear need for a much broader policy response - working to improve the availability, accessibility and affordability of accommodation, working to address the root causes of homelessness, and to ensure a robust welfare safety net, before local authority duties can be performed in such a way as to substantively reduce homelessness.